A novel carbon-assisted chemical vapor deposition growth of large-area uniform monolayer mos2 and ws2 - Bae, Jeonghwan; Yoo, Youngdong (Nanomaterials, 2021)
Monolayer MoS2 can be used for various applications such as flexible optoelectronics and electronics due to its exceptional optical and electronic properties. For these applications, large-area synthesis of high-quality monolayer MoS2 is highly desirable. However, the conventional chemical vapor deposition (CVD) method using MoO3 and S powder has shown limitations in synthesizing high-quality monolayer MoS2 over a large area on a substrate. In this study, we present a novel carbon cloth-assisted CVD method for large-area uniform synthesis of high-quality monolayer MoS2 . While the conventional CVD method produces thick MoS2 films in the center of the substrate and forms MoS2 monolayers at the edge of the thick MoS2 films, our carbon cloth-assisted CVD method uniformly grows high-quality monolayer MoS2 in the center of the substrate. The as-synthesized monolayer MoS2 was characterized in detail by Raman/photoluminescence spectroscopy, atomic force microscopy, and transmission electron microscopy. We reveal the growth process of monolayer MoS2 initiated from MoS2 seeds by synthesizing monolayer MoS2 with varying reaction times. In addition, we show that the CVD method employing carbon powder also produces uniform monolayer MoS2 without forming thick MoS2 films in the center of the substrate. This confirms that the large-area growth of monolayer MoS2 using the carbon cloth-assisted CVD method is mainly due to reducing properties of the carbon material, rather than the effect of covering the carbon cloth. Furthermore, we demonstrate that our carbon cloth-assisted CVD method is generally applicable to large-area uniform synthesis of other monolayer transition metal dichalcogenides, including monolayer WS2 .
Keywords: Carbon-assisted CVD; Growth mechanism; Monolayer; MoS2; WS2